The role of PM2.5 exposure in lung cancer: mechanisms, genetic factors, and clinical implications - Chi-Yuan Chen; Kuo-Yen Huang; Chin-Chuan Chen; Ya-Hsuan Chang; Hsin-Jung Li; Tong-Hong Wang; Pan-Chyr Yang (EMBO Molecular Medicine)
Abstract Lung cancer is one of the most critical global health threats, as the second most common cancer and leading cause of cancer deaths globally. While smoking is the primary risk factor, an increasing number of cases occur in nonsmokers, with lung cancer in nonsmokers (LCNS) now recognized as the fifth leading cause of cancer mortality worldwide. Recent evidence identifies air pollution, particularly fine particulate matter (PM2.5), as a significant risk factor in LCNS. PM2.5 can increase oxidative stress and inflammation, induce genetic alterations and activation of oncogenes (including the epidermal growth factor receptor, EGFR), and contribute to lung cancer progression. This review summarizes the current understanding of how exposure to PM2.5 induces lung carcinogenesis and accelerates lung cancer development. It underscores the importance of prevention and early detection while calling for targeted therapies to combat the detrimental effects of air pollution. An integrated approach that combines research, public health policy, and clinical practice is essential to reduce the lung cancer burden and improve outcomes for those affected by PM2.5 exposurrre.